PENDAMPINGAN PEMBELAJARAN BACA TULIS AL QURAN PADA SISWA SD NEGERI 2 KUWASEN JEPARA - Mahalli - Mahalli; Khalimatus Sadiyah; Sa’adatul Kholili (LPPM Universitas Abdurrab, 2021)
Students’ ability to read and write the Holy Quran is a basic skill that greatly supports the mastery of Islamic Religious Education (PAI) subject matter. Initial data shows that students in grade V.SD N 2 Kuwasen have low ability to read and write the Holy Quran, while the time allocation available in the elementary school curriculum structure and Islamic Education teachers are not sufficient to deal with this problem, so it requires special time outside intra-curricular hours. This community service aims to assist the fifth grade students of SD Negeri 2 Kuwasen in learning to read and write the Holy Quran by mentoring them in learning activities outside the intra curricular time. The results of this activity indicate that mentoring in BTQ learning has a positive impact in improving the reading and writing skills of the fifth grade students of SDN 2 Kuwasen. This can be seen by comparing the average pre-test scores with the average post-test scores